ABO blood type and stroke risk: the REasons for Geographic And Racial Differences in Stroke Study. (April 2014) - Zakai, N. A.; Judd, S. E.; Alexander, K.; McClure, L. A.; Kissela, B. M.; Howard, G.; Cushman, M.
Summary Background ABO blood type is an inherited trait associated with coagulation factor levels and vascular outcomes. Objectives To assess the association of blood type with stroke and whether blood type contributes to racial disparities in stroke in the United States. Patients and Methods The REasons for Geographic And Racial Differences in Stroke (REGARDS) Study recruited 30 239 participants between 2003 and 2007. Using a case‐cohort design, blood type was genotyped in 646 participants with stroke and a 1104‐participant cohort random sample. Cox models that adjusted for Framingham stroke risk factors were used to assess the association of blood type with stroke. Results During 5.8 years of follow‐up, blood types A or B vs. type O were not associated with stroke. Blood type AB vs. O was associated with an increased risk of stroke (adjusted hazard ratio [HR] 1.83, 95% confidence interval [CI] 1.01–3.30). The association of blood type AB vs. O was greater in those without diabetes (adjusted HR 3.33, 95% CI 1.61–6.88) than those with diabetes (adjusted HR 0.49, 95% CI 0.17–1.44) (P interaction = 0.02). Factor VIII levels accounted for 60% (95% CI 11%–98%) of the association of AB blood type and stroke risk. Conclusion Blood type AB is associated with an increased risk of stroke that is not attenuated by conventional stroke risk factors, and factor VIII levels were associated with 60% of the association. While blood type AB is rare in the US population, it is a significant stroke risk factor and may play an important role in stroke risk in these individuals.